Interplay between Heat Shock Proteins, Inflammation and Pain: A Promising Therapeutic Approach - aminian, Ahmad R.; Forouzanfar, Fatemeh (Current Molecular Pharmacology, 2022)
Heat Shock Proteins (HSPs) are important molecular chaperones that facilitate many functions of the cells. They also play a pivotal role in cell survival, especially in the presence of stressors, including nutritional deprivation, lack of oxygen, fever, alcohol, inflammation, oxidative stress, heavy metals, as well as conditions that cause injury and necrosis. In the face of a painful stimulus encounter, many factors could be associated with pain that may include nitric oxide, excitatory amino acids, reactive oxygen species (ROS) formation, prostaglandins, and inflammatory cytokines. One influential factor affecting pain reduction is the expression of HSPs that act as a ROS scavenger, regulate the inflammatory cytokines, and reduce pain responses subsequently. Hence, we assembled information on the painkilling attributes of HSPs. In this field of research, new painkillers could be developed by targetting HSPs to alleviate pain and widen our grasp of pain in pathological conditions and neurological diseases.
Keywords: Heat shock proteins